Synthesis and evaluation of a series of 6-chloro-4-methylumbelliferyl glycosides as fluorogenic reagents for screening metagenomic libraries for glycosidase activity. (8th February 2016) - Chen, Hong-Ming; Armstrong, Zachary; Hallam, Steven J.; Withers, Stephen G.
Highlights: Sensitive fluorogenic substrates are required for high-throughput screening of enzyme libraries. The synthesis of a series of nine different glycosides bearing a 6-chloro-4-methylumbelliferyl chromogen is described. These substrates are used in a pooled fashion to screen a small expressed metagenomic library. Simple deconvolution identified the individual glycosidase activities. Graphical abstract: Abstract: Screening of large enzyme libraries such as those derived from metagenomic sources requires sensitive substrates. Fluorogenic glycosides typically offer the best sensitivity but typically must be used in a stopped format to generate good signal. Use of fluorescent phenols of pKa < 7, such as halogenated coumarins, allows direct screening at neutral pH. The synthesis and characterisation of a set of nine different glycosides of 6-chloro-4-methylumbelliferone are described. The use of these substrates in a pooled format for screening of expressed metagenomic libraries yielded a "hit rate" of 1 in 60. Hits were then readily deconvoluted with the individual substrates in a single plate to identify specific activities within each clone. The use of such a collection of substrates greatly accelerates the screening process.